Implementasi pendekatan kontekstual pada model pembelajaran scaffolding - Yoni Sunaryo; Ai Tusi Fatimah (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2018)
The purpose of this study was to find out an overview of an innovation learning model in the form of the application of the Contextual Approach applied to the Scaffolding Learning Model. This innovation is a creativity that is carried out in classroom learning to create a combination of an approach and a learning model that facilitates students to explore their thinking skills, both high-level thinking and low-level thinking. This research is a descriptive research. The results obtained from this study are a syntax of the application of the Contextual Approach to the Scaffolding Learning Model that can be made an alternative in the implementation of learning by the instructors. The learning stages are: 1) Explaining learning material; 2) Grouping students according to their ZPD; 3) Provide learning tasks in the form of tiered questions related to learning material; 4) Encourage students to work and learn to solve problems independently in groups; 5) Providing assistance in the form of guidance, motivation, giving examples, keywords or other things that can lure students towards learning independence; 6) Direct students who have high ZPD to help students who have low ZPD; 7) Summing up lessons and giving assignments; 8) Summing up lessons and giving assignments and 9) Actual assessment.Keywords: Contextual Approach; Scaffolding Learning Model